Emotion Regulation Strategies In Women Who Married At Early Age - Zaen Musyrifin; Afifah Nur Hanifah (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Early marriage poses negative impacts on various aspects of life, including health, finance, and psychology. However, the number of underage marriage cases is increasing. This study aimed to identify emotion regulation strategies used by women who married young to find the meaning of happiness in marriage. The approach used was qualitative with the case study method. Data collection was carried out through interviews, observation, and documentation. Three female respondents were involved in the study, all married under 19. The results showed that the three informants used five strategies to manage their emotions, but their implementation differed according to their personal backgrounds and capacities. These five emotional regulation strategies can help them find the meaning of happiness in their young marriage.